Content analysis of cannabis vaping videos on YouTube. (9th February 2021) - Lim, Carmen C. W.; Leung, Janni; Chung, Jack Yiu Chak; Sun, Tianze; Gartner, Coral; Connor, Jason; Hall, Wayne; Chiu, Vivian; Tisdale, Calvert; Stjepanović, Daniel; Chan, Gary
Abstract: Background and Aims: There has been an increase in the potency of cannabis during the last two decades and adoption of a novel method of administration—vaping. YouTube, a social media platform, has become a popular source to access cannabis‐related information. This study aimed to identify cannabis vaping YouTube videos from 2016 to 2020 and examine the themes and metrics. Design: Cross‐sectional sample of 200 YouTube videos. Setting: YouTube, an on‐line video sharing platform. Measurements: Videos related to cannabis vaping were identified using the search terms: 'vaping cannabis', 'vaping weed', 'vaping marijuana' and 'vaping THC' [tetrahydrocannabinol]. Videos were independently coded by two researchers. The number of views, likes, dislikes and comments were also collected. Robust regression was used to analyse the relationship between identified video themes and video metrics. Findings: Six themes were identified: 'advertisement', 'product review', 'celebratory', 'reflective', 'how‐to' and 'warning'. The 'how‐to' and 'celebratory' videos received the highest number of views and likes. The most popular video was viewed more than 4 000 000 times. Many videos portrayed risky behaviour (e.g. vaping a whole THC cartridge in a single setting). Fifty‐two percent of these videos had no age access restrictions. The robust regression model also found that engagement metric was positively associated with 'reflective' videos and negatively associated with 'advertisement' videos. Conclusions: A large number of videos on cannabis vaping are available on‐line without age‐restriction. Videos that portrayed risky behaviour appear to be prevalent.